A novel verification framework to analyse security attacks in a fingerprint authentication system. (1st November 2022) - Harikrishnan, D.; Sunilkumar, N.; Joseph, Shelbi; Nair, Kishor Krishnan
The security vulnerabilities and flaws in the existing biometric fingerprint authentication system (FAS) are effectively overcome using the one time finger code (OTFC). Based on this OTFC technique, a new verification model is proposed in this work which is capable of evaluating and analysing the susceptibility of system to common security attacks. For verification and validation compliance, an integrated security framework with novel security protocol along with generation of a unique encryption key named terminal key is conceptualised and implemented. The exposure of the system to various security attacks are experimentally computed by measuring avalanche effect, which fetches an average value of 63.52%. Also, the severity of attack is verified by calculating base score obtained as 3, which is less in comparison with conventional systems. Hence it concludes that proposed FAS with new verification framework yields better results on exposure to common security threats than the conventional one.